RNA-Seq Analysis Revealed the Virulence Regulatory Network Mediated by the Ferric Uptake Regulator (Fur) in Apostichopus japonicus Pathogenesis Induced by Vibrio splendidus - Changyu Liao; Lincheng Hu; Si Zhu; Weikang Liang; Lei Yang; Chenghua Li (Microorganisms, 2025)
The uptake and utilization of iron by bacteria must be strictly controlled. The ferric uptake regulator (Fur) is a global transcription factor widely present in bacteria that can perceive cellular iron levels and adjust the expressions of various genes accordingly. Our earlier research demonstrated that the knockdown of the fur gene in Vibrio splendidus significantly reduced its lethality to Apostichopus japonicus. Although the functions and mechanisms of Fur in regulating bacterial virulence genes have been extensively studied, its virulence regulatory network during V. splendidus pathogenesis in A. japonicus remains unclear. In this article, transcriptome sequencing analysis of V. splendidus under different iron conditions reveals substantial differential gene expressions in the simulated pathogenic environments, identifying 1185 differentially expressed genes, including 198 downregulated and 987 upregulated genes. Comparative analysis between wild-type and Vsfur knockdown strains shows that Vsfur knockdown altered the expression of 3593 genes in V. splendidus, with the most significant differential expression observed under simulated pathogenic conditions (1030 upregulated and 72 downregulated). KEGG enrichment analysis indicates that Vsfur knockdown caused significant gene enrichment in the flagellar assembly pathway and bacterial secretion system, critically impairing flagellar synthesis and secretion system function in V. splendidus. Eight genes selected for qRT-PCR validation showed expression levels in line with the RNA-seq results. Consistent with the transcriptomic results, Vsfur knockdown resulted in reduced antioxidant capacity, bacterial competitiveness, and cytotoxicity in V. splendidus. These findings elucidate the virulence regulatory mechanism of Fur in V. splendidus and provide a reference for understanding the occurrence of A. japonicus skin ulcer syndrome.